EDUCATION FOR ALL: A STUDY OF ORANG RIMBA IN TANAH MENANG, BUNGKU’S VILLAGE, BATANGHARI DISTRICT, JAMBI PROVINCE INDONESIA - Suryawahyuni Latief; Santi Hendrayani; Puji Lestari (International Journal of Southeast Asia, 2020)
The purpose of this study is to describe education for the aboriginal community in Tanah Menang, Bungku’s Village, Batanghari District, Jambi Province, Indonesia. This study employs a descriptive qualitative approach. We collected data through interviews, observations, and documents. The results found that: 1) the education for Orang Rimba in Tanah Menang provides since 2017 that focused on a base education; 2) the teacher creates the lesson material through the picture, and puzzle fixed with their environment; 3) the primary method of learning is teacher-centered, 4) the average of students age is 10 to 20 years old; 5) the learning process conveyed in bilingual, heritage language of Orang Rimba and Bahasa.